Pengawasan Transportasi Laut demi Mewujudkan Keselamatan dan Keamanan Pelayaran Nasional - Hana Faridah , Hana Faridah; Fajarwati, Rona Apriana (Jurnal Keamanan Nasional, 2022)
This study aims to study and analyze forms of sea transportation supervision in order to realize the safety and security of national shipping based on laws and regulations. This study uses a normative juridical approach with descriptive analysis. The data used is secondary data obtained through a literature study, which is then analyzed qualitatively. Based on research, law enforcement implies that there is a demand for the ability to maintain and supervise compliance with certain legal provisions in the waters of Indonesia’s national jurisdiction. Guidance in the shipping sector is controlled by the state and the guidance is carried out by the government, while shipping guidance consists of: regulation, supervision, and control. The factors that become obstacles in law enforcement for the safety of sea transportation service users can be carried out by conducting periodic seafarer resource training and carried out seriously and seriously and with full responsibility for the creation of expertise and skills based on the certificate held by the captain, Ship Officers, and Ship’s Crew.